Respostas
respondido por:
1
Resposta:
ײ+2×+3×+6=6
ײ+5×+6=6
ײ+5×=6-6
ײ+5×=0
elianejandira2812:
: )
respondido por:
1
Resposta:
raizes são (0) e (-5)
Explicação passo-a-passo:
(x+3) . (x+2) = 6
x² + 5x + 6 = 6
x² + 5x + 6 - 6 = 0
x² + 5x = 0 ---> eq. do2º incompleta
a = 1 b = 5 c = 0 Δ= b²-4ac ∴Δ = 5² - 4 . 1 . 0 ∴Δ = 25
x = -b+-√Δ/2a ∴ x = -5 +- √25 / 2.1 ∴ x = -5 +- 5 / 2
x' = -5+5/2 = 0
x'' = -5 - 5 /2 = -10/2 = -5
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás